2001
DOI: 10.1016/s1074-7613(01)00234-5
|View full text |Cite
|
Sign up to set email alerts
|

The Immunological Synapse of CTL Contains a Secretory Domain and Membrane Bridges

Abstract: Cytotoxic T lymphocytes (CTL) rapidly destroy their targets. Here we show that although target cell death occurs within 5 min of CTL-target cell contact, an immunological synapse similar to that seen in CD4 cells rapidly forms in CTL, with a ring of adhesion proteins surrounding an inner signaling molecule domain. Lytic granule secretion occurs in a separate domain within the adhesion ring, maintaining signaling protein organization during exocytosis. Live and fixed cell studies show target cell plasma membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
700
2
13

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 732 publications
(754 citation statements)
references
References 31 publications
32
700
2
13
Order By: Relevance
“…It is uncertain how often large amounts of IL-2 or IL-15 are readily available in vivo. IL-2 is vectorially secreted by CD4 + T helper cells [58,59], suggesting that exposure is normally carefully regulated. However, because IL-2 is a secreted protein, localized excesses are possible.…”
Section: Discussionmentioning
confidence: 99%
“…It is uncertain how often large amounts of IL-2 or IL-15 are readily available in vivo. IL-2 is vectorially secreted by CD4 + T helper cells [58,59], suggesting that exposure is normally carefully regulated. However, because IL-2 is a secreted protein, localized excesses are possible.…”
Section: Discussionmentioning
confidence: 99%
“…These nanotubes were shown to facilitate the transfer of lipid organelles between cells through actindependent mechanism. Nanotube structures were also reported to connect a wide range of immune cells, such as T cells, B cells, NK cells, and monocytes (24,75). In the event of disassembly of immunological synapse, formation of membrane nanotubes was observed between B cells and NK cells (76).…”
Section: Membrane Nanotube Formationmentioning
confidence: 98%
“…Of late new reports of intercellular membrane transfer started pouring in. It was demonstrated that T cells can acquire not only the MHC class I and class II proteins (18,19), but also the costimulatory proteins (20)(21)(22), the membrane fragments (23,24) from APCs and the proteins from endothelial cells (25). Till recently, the protein transfer by trogocytosis is believed to be unidirectional in murine system (1).…”
Section: Trogocytosis a Widespread Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…Ce mécanisme de maturation tardive pourrait également permettre de contrôler le nombre de granules cytotoxiques capables d'excréter leur contenu à la SI, et ainsi réguler précisément l'intensité d'une réponse cytotoxique. Il est également possible que ce même mécanisme de contrôle permette aux cellules cytotoxiques de disposer d'une fonction cytotoxique itérative leur conférant ce comportement de « tueur en série» qui les caractérise [2,10]. …”
Section: Discussionunclassified